The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1136/bjsports-2018-100350
|View full text |Cite
|
Sign up to set email alerts
|

Physically active individuals have a 23% lower risk of any colorectal neoplasia and a 27% lower risk of advanced colorectal neoplasia than their non-active counterparts: systematic review and meta-analysis of observational studies

Abstract: BackgroundFew studies have examined the associations between physical activity (PA), sedentary behaviour (SB) and risk of colorectal neoplasia (CN).MethodsWe systematically searched Medline, Embase, PsyInfo, Cochrane and other sources from their inception to 30 September 2018 for cohort, case-control and cross-sectional studies that evaluated these associations in asymptomatic, average-risk subjects. Random-effect models were used to estimate relative risks (RRs) of any-type CN, advanced CN, and non-advanced C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 70 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Bailey et al also found an increase in incident CVD risk (HR = 1.29 (95% CI, 1.27 to 1.30) with total sitting, which was attenuated following statistical adjustment for physical activity (HR = 1.14 (95% CI, 1.04 to 1.23)) [24]. Four new reviews [25,26,31,36] reporting on sedentary behaviour and cancer incidence all had very low to low certainty ratings, mostly attributable to a lack of adjustment for confounding variables, indirectness in terms of diversity of outcome assessment, and high statistical heterogeneity. However, evidence from three metaanalyses [37][38][39] previously summarized [9] provided moderate certainty evidence for an association between sedentary behaviour and type cancer incidence (endometrial, colon, and lung cancers).…”
Section: B-d)mentioning
confidence: 96%
“…Bailey et al also found an increase in incident CVD risk (HR = 1.29 (95% CI, 1.27 to 1.30) with total sitting, which was attenuated following statistical adjustment for physical activity (HR = 1.14 (95% CI, 1.04 to 1.23)) [24]. Four new reviews [25,26,31,36] reporting on sedentary behaviour and cancer incidence all had very low to low certainty ratings, mostly attributable to a lack of adjustment for confounding variables, indirectness in terms of diversity of outcome assessment, and high statistical heterogeneity. However, evidence from three metaanalyses [37][38][39] previously summarized [9] provided moderate certainty evidence for an association between sedentary behaviour and type cancer incidence (endometrial, colon, and lung cancers).…”
Section: B-d)mentioning
confidence: 96%
“…Systematic research by Wang et al from 2018 was produced after searching Medline, Embase, PsyInfo, Cochrane, and other databases and included 32 observational studies, out of which 17 were cross-sectional, ten case-control, and five cohorts (9). It concluded that in people with the highest level of physical activity, there was a 23% lower relative risk of any colon cancer (CRC) and 27% for advanced CRC than those with the lowest level of physical activity.…”
Section: Resultsmentioning
confidence: 99%
“…Published articles on circulating miRNAs associated with cancer were selected on PubMed by searching for “serum miRNAs”, “serum microRNAs”, “plasma miRNAs”, “plasma microRNAs”, “circulating miRNAs”, “circulating microRNAs” with “cancer diagnosis” for five cancers: lung cancer (LC), prostate cancer (PC), colon cancer (CC), liver cancer (HC) and gastroesophageal cancer (GEC) and related subtypes. These cancers were chosen as the five most frequent cancers in males worldwide, according to the “Global Cancer Observatory” ( , accessed on 31 December 2020), for which exist evidence, through meta-analysis (published from 2010 to 2020), on association with physical activity (all-cancer risk/mortality [ 25 , 26 , 27 , 28 , 29 ]; LC [ 30 , 31 ]; PC [ 32 ]; CC [ 33 , 34 , 35 ]; HC [ 36 ]; GEC [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]). Only studies on human, published from 2010, and demonstrating a clinical relevance for single serum/plasma miRNA or serum/plasma miRNA signatures including at least one of the modulated miRNAs in our trained cohort were considered.…”
Section: Methodsmentioning
confidence: 99%